The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1002/pds.5126
|View full text |Cite
|
Sign up to set email alerts
|

Validation of algorithms to estimate gestational age at birth in the Medicaid Analytic eXtract—Quantifying the misclassification of maternal drug exposure during pregnancy

Abstract: Purpose: Accurate ascertainment of gestational age (GA) has been a challenge in perinatal epidemiologic research. To date, no study has validated GA algorithms in Medicaid Analytic eXtract (MAX). Methods: We linked livebirths of mothers enrolled in Medicaid ≥30 days after delivery in 1999-2010 MAX to state birth certificates. We used clinical/obstetric estimate of gestation on the birth certificates as gold standard to validate claims-based GA algorithms. We calculated the proportions of deliveries with algori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 28 publications
(57 reference statements)
0
24
0
Order By: Relevance
“…Based on previous literature, estimation of conception will have varying degrees of accuracy for each type of pregnancy endpoint. 6 , 22 In our pregnancy identification algorithm, we assigned gestational age for live-birth episodes based on an algorithm of ICD codes indicating gestational age or preterm status, and the overall agreement against birth certificates is reported to be >93% in the Medicaid database. 22 For ectopic pregnancy, induced/spontaneous abortion, and stillbirth, we used fixed values for gestational age (8, 10, and 28 weeks, respectively) similar to previous literature.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Based on previous literature, estimation of conception will have varying degrees of accuracy for each type of pregnancy endpoint. 6 , 22 In our pregnancy identification algorithm, we assigned gestational age for live-birth episodes based on an algorithm of ICD codes indicating gestational age or preterm status, and the overall agreement against birth certificates is reported to be >93% in the Medicaid database. 22 For ectopic pregnancy, induced/spontaneous abortion, and stillbirth, we used fixed values for gestational age (8, 10, and 28 weeks, respectively) similar to previous literature.…”
Section: Discussionmentioning
confidence: 99%
“… 6 , 22 In our pregnancy identification algorithm, we assigned gestational age for live-birth episodes based on an algorithm of ICD codes indicating gestational age or preterm status, and the overall agreement against birth certificates is reported to be >93% in the Medicaid database. 22 For ectopic pregnancy, induced/spontaneous abortion, and stillbirth, we used fixed values for gestational age (8, 10, and 28 weeks, respectively) similar to previous literature. 6 , 7 This approach has shown a moderate agreement both against medical charts (70% for ectopic pregnancy and 67% for spontaneous abortions within four weeks) 7 , and a cohort of in-vitro fertilization patients (77% agreement for ectopic pregnancy, 47% for stillbirth, and 36% for abortions cases).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The study outcome was conception during the exposure period. To estimate conception date, we used an algorithm based on previous validation studies that identified pregnancy episodes among WCBP [13][14][15][16].…”
Section: Outcome Definitionmentioning
confidence: 99%